Effect Of Leg Vest And Rubber Load Training On The Sickle Kick Ability Of Psht Pencak Silat Athletes Of Samarinda City - Didik Cahyono; Muhammad Abdurrochim (CV. AFDIFAL MAJU BERKAH, 2022)
This study was submitted to obtain information about the influence of the use of foot and rubber on the ability of sickle kicks in PSHT martial arts athletes. The type of research used is field experiment research, simple in this study using psht Samarinda martial arts athletes as many as 40 people of the male sex, Based on the results of the research price t calculate for the influence of foot training on the improvement of kicking ability. sickle = -17.22, while for t calculate the effect of rubber weight training = -15.41, and for t calculate between the influence of foot load training and rubber load is, 3.14 there is a significant relationship between variables in the test, then In this study, there were 3 results, namely: there is an influence of foot weight training on the ability of sickle kicks in PSHT athletes, there is an influence of rubber weight training on the sickle kick ability of PSHT athletes, and there are differences in the influence of foot weight training and rubber weight training, and foot weight training is better than rubber weight training on the sickle kick ability of PSHT athletes Samarinda.